UPAYA PEMERINTAH KOTA PADANG DALAM MEMBERDAYAKAN NELAYAN TRADISIONAL DI PANTAI MUARO LASAK KOTA PADANG - Ovael Sandro Melta; M. Fachri Adnan (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2020)
This research was conducted at the Muaro Lasak beach in Padang City with the aim of describing the efforts of the Padang city government to empower traditional fishermen on the Muaro Lasak beach in Padang city. In addition to taking data on the coast of Muaro Lasak, research will also be conducted at the Padang City Maritime and Fisheries Office to obtain directed and precise research results to find out various phenomena and events that have occurred. The data collection technique was carried out by means of observation which meant that the data collection was carried out based on the results of the direct field that occurred at Muaro Lasak beach, Padang. The data analysis technique used in this study is descriptive analysis, which provides a holistic picture of the research. Observations are made directly and indirectly to get an accurate picture to find the right data and understand. With a variety of methods, it is hoped that this research can provide a clear and precise picture to meet the data and problems that will occur later. Government efforts in empowering traditional fishermen on the coast of Muaro Lasak, Padang city are going well because the Capture Fisheries Development Program or P3T provides possibilities, reinforcement, protection, support and maintenance that help traditional fishermen in solving their problems despite experiencing some obstacles that have not been can be resolved quickly. Through the Capture Fisheries Development Program, it will be seen how the response of traditional fishermen to the program and what effects will be felt by the traditional fishermen directly through observation later.